Breast tumor. Fundamentals of surgical treatment. - Mogrovejo Ugáz, Luis (2015)
The song "Mama Tumor" is very broad, and would require many pages to their development, so try to do a brief review and overview. Not beyond our understanding, the intention of the organizers, to address issues that are of practical interest, so it seems appropriate to highlight that endocrine dependence of the mammary gland to ovarian hormones, make those part of the female genital tract . That is why our gynecologists and obstetricians colleagues should be familiar with the management of breast disease, not only in the tumor, but endocrine, infectious, aesthetics, etc., ie, in what has become known lately Mastology in order to give a broader sense, and the Society of Obstetrics and Gynecology, assuming its role guiding our specialty, it is interested in promoting.